Economic analysis of resource conservation and household preferences attributes in Hadejia-Nguru Wetlands, Nigeria - Adamu, Abdullahi (2017)
Natural flood plain wetlands are among the most biologically productive and diverse ecosystems on earth. However, in spite of their importance in sustaining human welfare, they are the most threatened of all ecosystems. The objective of this study is to evaluate the economic benefit associated with resource conservation in Hadejia- Nguru wetland so as to provide policy-makers with much needed information on the economic value of the benefits generated by the sustainable management of the wetland. This study employed the most widely used non-market valuation techniques in measuring the economic value of natural resources. A face-to-face interview using a structured questionnaire of a dichotomous choice contingent valuation, choice experiment was employed to 393 households in communities residing within the wetlands (user category) and 405 households in upstream communities outside the wetland (Non-user category). Binary Logistic regression was employed in estimating the CVM model while Conditional logit model, random parameter logit model, and latent class model were employed for the choice experiment analysis in order to estimate attributes values and heterogeneity in the households’ preferences. Results from the choice experiment for the user category shows the preference of the wetlands’ attribute, with ‘improvement in productivity of the wetland as the most preferred attribute. From the non-user category, ‘tourism and recreation’ was the most preferred attribute. The result from the CVM model revealed that gender, age, education level, gross monthly income, bids amount, membership of environmental organisation, pro-environmental attitude and knowledge of the importance of the wetland were significant determinants of the willingness to pay conservation tax by the users for the sustenance of the wetland. On the other side, the significant determinants of willingness to pay donation by the non-users includes; gender, respondents’ age, gross monthly income, bid amount, household size, governmental trust, and proenvironmental attitude. The result also revealed that the users were willing to pay N 2,324.08 ≈ $ 7.62 per household for conservation of the wetland, while the non-users mean WTP amount was N 2290.31 (US$ 7.50). Based on the CVM result, the total use benefit of conservation of the wetland was approximately N 1,162,040,000 (US $ 3,809,967.21), while the total non-use benefit was estimated at N 29,366,540,335.11 (US $ 96,283,738.80). Therefore, the total benefit of conservation of the wetland was approximately N 30,528,580,335.11 (US $ 100,093,706.02). The study outcome would inform policy makers on the economic value of the wetland and to better their understanding on the consequences of present policies concerning wetland management. The study therefore recommended that the conservation of the wetlands should be considered as an integral system that would create institutional mechanisms, which will ensure the incorporation of local communities in decisionmaking and management of the wetland. This strategy would help in minimizing trade-offs and would promote synergies for sustainable wetland management.